LITERATURE REVIEW: CHALLENGES IN REACHING VOLUNTARY COUNSELING AND TESTING SERVICES FOR HUMAN IMMUNODEFICIENCY VIRUS SUFFERERS - Rohi, Yublina; B.T. Liunokas, Oklan; Christina Endang S., Maria; Pekabanda, Kartini; Toru, Veronika; Radandima, Ester (Poltekkes Kemenkes Kupang, 2025)
Background: Human Immunodeficiency Virus (HIV) is a disease that works by damaging the body's immune system so that patients are susceptible to opportunistic infectious diseases when the number of CD4 (white blood cells or lymphhocyte/T-cells) decreases or the viral load level increases. Objective: To identify challenges in achieving voluntary counseling and testing services for people with human immunodeficiency virus. Methods: literature review, literature search process using Google Scholar and Pubmed databases with the keyword 'Challengesi in Reaching Voluntary Counseling and Testing Services for Human Immunodeficiency Virus Sufferers'. The inclusion criteria are journals published in the 2021-2024 range, journal types of articles with quantitative, qualitative, empirical research methods, pdf full text journals, articles taken are national and international journal articles. Results: The challenges in achieving voluntary counseling and testing services for people with HIV are influenced by several things, including lack of cost, limited provision of logistics for examinations, stigma and discrimination both from patients and the community, including health workers, knowledge about HIV in at-risk people as well as the community, and limitedservice facilities and health human resources that are still limited both in terms of number and knowledge of VCT.